ADF-STEM imaging of nascent phases and extended disorder within the Mo–V–Nb–Te–O catalyst system - Vogt, T; Blom, D; Jones, L; Buttrey, D (Springer US, 2016)
Materials investigated for their potential use as heterogeneous selective oxidation catalysts may sometimes show highly ordered regions at the nanoscale which are embedded within highly disordered matrices from which they nucleate. These are often referred to as X-ray amorphous due to the lack of higher-order Bragg reflections; however, here we use annular dark-field scanning transmission electron microscopy (ADF-STEM) real space imaging to characterize the local structure of nanometer size domains of compositionally and structurally complex nascent oxide phases present in multi-phase disordered solids. These images have been obtained using aberration-corrected scanning transmission electron microscopy and point to its potential for local structural characterization where the synthesis conditions for a particular phase are not optimized or where self-assembly to extended structures has been locally hindered. Such studies may lead to identification of new catalysts, provided their targeted synthesis can be scaled up.